(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2008)
The purpose of this paper is to philosophically explore the Earth Charter as a cosmopolitan ethical framework for a pedagogy of peace. The Earth Charter constitutes a powerful articulation of a framework of cosmopolitan ethical principles for a just, peaceful, and ecologically sustainable society. It is a deliberative product of a globalcivil society, derived from cross-cultural dialogue. It constitutes an “actually existing” cosmopolitan ethic. This paper will articulate the cosmopolitan ethics of the Earth Charter and as well as exploring it’s potential as a foundation for a pedagogy of peace.